Hybrid Flow Architecture for Stable and Scalable Routing in Named Data Networks - P. Durgaprasad; K. Kranthi Kumar (International Journal of Advances in Applied Sciences, 2016)
The named data network is a new technology in routing were its forwarding plane helps us to recover the data on its own when the network failures occur.in this NDN the major issue are when the data is sent from one network to the other the data flow is not stable. By major survey we came to know that routing protocols plays a major role for the stable and scalable data flow. This routing protocols and be classified by forwarding process and also network topologies were the protocols have the data that can be retrieved back whenever the network faults occur. In this paper we proposed that hybrid flow architecture, network topologies and routing protocols are improved to get the stable and scalable routing when the data flow is interrupted.